Sulfurized Steel Nanoparticles: A Degradative Byproduct of ZrS2 CVD with Promising Fenton‐Type Catalytic Activity. Issue 4 (11th February 2022) - Currie, Taylor M.; Narkar, Ameya R.; Rudawski, Nicholas G.; Bryant, Jacob T.; Uribe‐Romo, Fernando J.; Shultz, Lorianne R.; Jurca, Titel
Abstract: Chemical vapor deposition (CVD), is an attractive method for the growth of two‐dimensional (2D) materials such as transition metal dichalcogenides (TMDCs). However, it is an inherently wasteful process; the majority of chemical precursors end up in the waste stream and their corrosive nature deteriorates reactor components. While exploring the thermal CVD growth of ZrS2, the resulting corrosion build up on the downstream stainless‐steel (SS) reactor components was collected and studied. Characterization of this material confirmed the presence of nanoplates composed of evenly distributed elements that constitute SS along with Cl, S, and trace Zr from the precursors. The material proved remarkably active as a photo‐Fenton type catalyst for the aqueous degradation of methylene blue. Harvesting and upcycling this overlooked nanomaterial will reduce waste and concomitantly add value and enhance the sustainability of the overall TMDC fabrication process. Abstract : Chemical vapor deposition (CVD) is an inherently wasteful process; most chemical precursors end up in the waste stream and the corrosive environment gradually degrades the stainless‐steel reactor components. Herein, the corroded material was harvested, studied, and successfully applied towards photo‐Fenton type catalysis. Upcycling a conventionally discarded material adds significant value and enhances the overall sustainability of the CVD process.